Assessing spatio-temporal dynamics of large airport’s surface stability - Yagmur, Nur; Erten, Esra; Musaoglu, Nebiye; Safak, Erdal (Informa UK Limited, 2022)
© 2022 Informa UK Limited, trading as Taylor & Francis Group.Istanbul Airport will be one of the biggest airports in the world when the construction in old open-pit mining areas which turned into wetlands is completed. To investigate the structural health monitoring of the Istanbul Airport, firstly the temporal evaluation of land use/land cover (LULC) in the region was generated for determining reclaimed lands using Random Forest classifier with Landsat images between 1984 and 2020. The outcomes were then examined with results of multi-temporal Interferometric Synthetic Aperture Radar (InSAR) methods, namely Small Baseline Subset (SBAS) for general displacement overview and Persistent Scatterer Interferometry (PSI) for detailed analysis of the settlement rate in the airport and runways which were applied to Sentinel-1 images. Both of the methods showed similar results for the same regionsand it is determined that there are movements up to 10 mm in Runway A and Runway B and more than 20 mm subsidence in Runway C.